Effects of Strong Turbulence on the Spiral Plane Mode of Whittaker–Gaussian Beam through Terrene-Atmosphere*Supported by the Fundamental Research Funds for the Central Universities under Grant No JUSRP51517, and the Graduate Student Research Innovation Project of Jiangsu-Province General University under Grant No KYLX15_1187. (May 2016) - Li 李, Ye 烨; Zhang 张, Yi-Xin 逸新
Abstract : The analytic formulae of probability distribution of spiral plane modes for the Whittaker–Gaussian (WG) beams with orbital angular momentum (OAM) in strong turbulence regime are modeled based on the modified Rytov approximation. Numerical results show that the crosstalk range of OAM modes in the vicinity of signal mode increases with the increasing refractive-index construction parameter. However, effects of change of the width of the Gaussian envelope and the parameter W0 of WG beams on normalization energy weight of signal mode can be ignored. We find theoretically that signal spiral plane mode of WG beams at each OAM level approximatively has the same normalization energy weight, implying that the channels with WG (pseudo non-diffraction) beam have higher channel capacity than the channels with the Laguerre–Gaussian beam.